Respuesta :
4 = 7 - 3
1 = 4 - 3
-2 = 1 - 3
-5 = -2 - 3
=> An = A (n-1) - 3, where A1 = 7
The next term is A6 = A5 - 3 = - 5 - 3 = - 8
So the answer is the fourth option.
1 = 4 - 3
-2 = 1 - 3
-5 = -2 - 3
=> An = A (n-1) - 3, where A1 = 7
The next term is A6 = A5 - 3 = - 5 - 3 = - 8
So the answer is the fourth option.
Answer: [tex]\\\Rightarrow\ a_n=a_{n-1}-3[/tex], where [tex]a-1 = 7[/tex]
The next term is -8.
Step-by-step explanation:
The given sequence is 7, 4, 1, –2, –5, ................
Here, the first term is [tex]a_1=7[/tex]
The second term is [tex]a_2=4[/tex]
The difference =[tex]a_2-a_1=4-7=-3[/tex]
Similarly, [tex]a_3-a_2=1-4=-3[/tex]
[tex]a_4-a_3=-2-1=-3[/tex] and so on.
Therefore, the recursive formula for the above sequence will be given by :-
[tex]a_n=a_{n-1}+d[/tex], where d is the common difference.
Since , d=-3
[tex]\\\Rightarrow\ a_n=a_{n-1}-3[/tex], where [tex]a-1 = 7[/tex]
The next term of the sequence is [tex]a_6=a_5-3=-5-3=-8[/tex]